2020
DOI: 10.3390/ijms21072603
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Erythroid Differentiation Regulator 1 (ERDR1) in the Control of Proliferation and Photodynamic Therapy (PDT) Response

Abstract: Erythroid differentiation regulator 1 (ERDR1) was newly identified as a secreted protein that plays an essential role in maintaining cell growth homeostasis. ERDR1 enhances apoptosis at high cell densities, leading to the inhibition of cell survival. Exogenous ERDR1 treatment decreases cancer cell proliferation and tumor growth as a result of increased apoptosis via the regulation of apoptosis-related gene expression. Moreover, ERDR1 plays a pivotal role in skin diseases; ERDR1 expression in actinic keratosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The erythroblast membrane-associated protein ( ERMAP ) and the erythroid differentiation regulator ( Erdr1 ) were among the few upregulated genes in response to lethal IR exposure. These two genes encode proteins that modulate erythrocyte adhesion properties [ 82 ] and negatively regulate cell migration and regulation [ 83 ], respectively. Other erythrocyte-related genes such as the hemoglobin subunit α 1 and 2 ( HBA1 and 2 ), hemoglobin subunit β ( HBB ), hemopexin ( HPX ), heme binding protein 2 ( HEBP2 ), and hemojuvelin BMP co-receptor ( HJV ) were downregulated at all TPs after lethal IR exposure and sporadically at TPs of sublethal exposures including early TPs.…”
Section: Discussionmentioning
confidence: 99%
“…The erythroblast membrane-associated protein ( ERMAP ) and the erythroid differentiation regulator ( Erdr1 ) were among the few upregulated genes in response to lethal IR exposure. These two genes encode proteins that modulate erythrocyte adhesion properties [ 82 ] and negatively regulate cell migration and regulation [ 83 ], respectively. Other erythrocyte-related genes such as the hemoglobin subunit α 1 and 2 ( HBA1 and 2 ), hemoglobin subunit β ( HBB ), hemopexin ( HPX ), heme binding protein 2 ( HEBP2 ), and hemojuvelin BMP co-receptor ( HJV ) were downregulated at all TPs after lethal IR exposure and sporadically at TPs of sublethal exposures including early TPs.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies also revealed that the probiotic L. reuteri also can stimulate the Wnt/β-catenin signaling pathway contributing to further stimulation of the epithelial proliferation via Lgr5 ISCs (91). Additionally, erythroid differentiation regulator-1 [Erdr1] is an important protein that plays many roles in cell growth homeostasis such as cell proliferation, regulating cell apoptosis, and regeneration rate (92). Expression of this protein is only achieved with the help of the gut microbiota that inhabits the intestine during the early years of life, which in particular helps regulate the role of the protein expression in the proliferation of Lgr5 ISCs (93).…”
Section: Immunomodulatory and Regenerative Effectsmentioning
confidence: 99%
“…This innovative technique is attractive in terms of specificity and for not damaging healthy cells compared to other cancer treatments. Despite the rapid development of modern ways fighting cancer, classic methods such as chemotherapy remain the only option in the treatment of certain types of cancer, e.g., leukemia [ 2 , 3 ]. The first records of the healing properties of the Sun’s rays date back to ancient times.…”
Section: Introductionmentioning
confidence: 99%